Effectiveness of an Interventional Program on Nurses` Practices Toward Post-Operative Intravenous Infusion of Infants with Tracheoesophageal Fistula - Salih, Abdulrahman Hussein; Obaid, Ali Abdul Razzak (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): The study aims to determine the effectiveness of the intervention program on nurses’ practices regarding the post-operative Intravenous Infusion of infants with tracheoesophageal fistula. Methods: A Quantitative, pre-experimental design, was conducted has been by using the one-group test-retest method, pre-test, post-test 1, and post-test 2. An observational checklist has been adapted to collect the data before and after implementing the Interventional program. A non-probability (convenience) sample consists of all nurses in the Neonatal Intensive Care Unit. After explaining the nature, significance, and objectives of the study to every nurse in the Neonatal Intensive Care Unit, each nurse consented to participate in the research. The data analysis was performed using the social sciences software, version 23. Results: A statistically significant difference exists between the levels of practice scores in the pre-test post-test I and post-test II. The result findings revealed a significant improvement in the nurse’s practices after the implementation of an Interventional program through Analysis of Variance. Conclusions: The study determined that the intervention program is an effective means of enhancing the post-operative practices of nurses for neonates with tracheoesophageal fistula. Recommendations: The study recommended that continuous intervention courses be designed, structured, and implemented regularly for the benefit of nurses who perform such procedures, monitoring, and evaluation of nurses regarding procedures for the post-operative care of infants with tracheoesophageal fistula.